PROTEIN RESIDUE ANALYSIS OF ARTIFACTS FROM SITES HHOS-9, HHOS-11, HHOS-14, HIOR-3, AND HIOR-5 FOR THE HUSKY SUNRISE THERMAL SAGD PROJECT, ALBERTA, CANADA - Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
Artifacts from sites HhOs-9, HhOs-11, HhOs-14, HiOr-3, and HiOr-5 in the vicinity of Fort McMurray, Alberta, were tested for possible protein residues. The artifacts from these sites appear to date to approximately 9000 and 7000 BP. Analysis of protein residues from the artifacts' surface can provide information concerning processing/hunting of animals with these tools.